Variants on the UBE2L3/YDJC Autoimmune Disease Risk Haplotype Increase UBE2L3 Expression by Modulating CCCTC‐Binding Factor and YY1 Binding. Issue 1 (13th December 2021) - Gopalakrishnan, Jaanam; Tessneer, Kandice L.; Fu, Yao; Pasula, Satish; Pelikan, Richard C.; Kelly, Jennifer A.; Wiley, Graham B.; Gaffney, Patrick M.
Abstract : Objective: Genetic variants spanning UBE2L3 are associated with increased expression of the UBE2L3 ‐encoded E2 ubiquitin‐conjugating enzyme H7 (UbcH7), which facilitates activation of proinflammatory NF‐κB signaling and susceptibility to autoimmune diseases. We undertook this study to delineate how genetic variants carried on the UBE2L3/YDJC autoimmune risk haplotype function to drive hypermorphic UBE2L3 expression. Methods: We used bioinformatic analyses, electrophoretic mobility shift assays, and luciferase reporter assays to identify and functionally characterize allele‐specific effects of risk variants positioned in chromatin accessible regions of immune cells. Chromatin conformation capture with quantitative polymerase chain reaction (3C‐qPCR), chromatin immunoprecipitation (ChIP)–qPCR, and small interfering RNA (siRNA) knockdown assays were performed on patient‐derived Epstein‐Barr virus–transformed B cells homozygous for the UBE2L3 / YDJC nonrisk or risk haplotype to determine if the risk haplotype increases UBE2L3 expression by altering the regulatory chromatin architecture in the region. Results: Of the 7 prioritized variants, 5 demonstrated allele‐specific increases in nuclear protein binding affinity and regulatory activity. High‐throughput sequencing of chromosome conformation capture coupled with ChIP (HiChIP) and 3C‐qPCR uncovered a long‐range interaction between the UBE2L3 promoter (rs140490, rs140491, rs11089620) and the downstream YDJC promoter (rs3747093) that was strengthened in the presence of the UBE2L3 / YDJC risk haplotype, and correlated with the loss of CCCTC‐binding factor (CTCF) and gain of YY1 binding at the risk alleles. Depleting YY1 by siRNA disrupted the long‐range interaction between the 2 promoters and reduced UBE2L3 expression. Conclusion: The UBE2L3 / YDJC autoimmune risk haplotype increases UBE2L3 expression through strengthening a YY1‐mediated interaction between the UBE2L3 and YDJC promoters.